A pecuária bovina em remanescente de floresta estacional no bioma Pampa: impactos na estrutura e diversidade - Stefanello, Maureen de Moraes (2020)
Cattle farming in forest ecosystems can produce different intensity disturbances, leading to changes in structure and floristic composition. Studies aiming to investigate the structure and understand the effects on the dynamics of forests used for this purpose are fundamental for the management of biodiversity in these areas. The objective of this study was to evaluate, from management records of different cattle occupancy rates, the impacts on the structure and diversity of a remnant of Seasonal Forest in the Pampa biome. The experiment was conducted in the municipality of São Nicolau, Rio Grande do Sul. Three areas of the remnant were compared, using 45-years of management history: (A1) area without the presence of cattle, (A2) area with a management history of low occupancy rates of cattle, and (A3) area with a management history of high occupancy rates of cattle. Vegetation surveys were carried out, divided into natural regeneration (0.1 m ≤ H < 3.0 m) (16 plots of 25 m² per area), understory vegetation (3.0 m ≤ H < 9.0 m), and canopy vegetation (9.0 m ≤ H) (16 plots of 150 m² per area). The plots located in areas A2 and A3 were isolated with a fence to exclude cattle and monitor passive restoration. In the vegetation survey, the numbers of individuals, species, and families was counted for each area and the phytosociological and ecological indices by stratum were calculated. The seed rain was collected and analyzed using 16 collectors of 1m² per area for 24 months. The monitoring of passive restoration was carried out in 16 fenced plots of 25m2 in A2 and A3, at three moments: 2014 (removal of cattle and isolation of areas), 2017 (three years of isolation), and 2019 (six years of isolation). The results point to floristic simplification in the vertical structure of the remnant in the area with a history of higher occupancy rates. Pasture use by cattle caused changes in canopy vegetation in relation to floristic composition and functional diversity. The results for the seed rain indicated that the impacts caused by cattle on A3 vegetation reduced the number of seeds and morphospecies due to the reduction in the number of plant individuals that make up the community. Passive restoration demonstrated a significant increase in the number of individuals, species, families, and taxonomic and functional diversity after three and six years of isolation. Thus, the history of management with high cattle occupancy rates demonstrated a greater impact on the density and richness of species and on the seed rain, while the history of management with low cattle occupancy rates did not cause damage to the taxonomic and functional diversity, this representing an alternative for conservationist management of the remaining forest in rural properties. Passive restoration showed promising results in the return, development, and diversity of natural regeneration in areas with cattle management. This technique can be recommended for environmental conditions similar to that of the current study, in projects for the recovery of Permanent Preservation Areas (PPA) with riparian vegetation and Legal Reserves (LR) in forest remnants in rural properties.